Making it work for me: beliefs about making a personal health record relevant and useable - Fiona Fylan; Lauren Caveney; Alastair Cartwright; Beth Fylan (BMC, 2018)
Abstract Background A Personal Health Record (PHR) is an electronic record that individuals use to manage and share their health information, e.g. data from their medical records and data collected by apps. However, engagement with their record can be low if people do not find it beneficial to their health, wellbeing or interactions with health and other services. We have explored the beliefs potential users have about a PHR, how it could be made personally relevant, and barriers to its use. Methods A qualitative design comprising eight focus groups, each with 6-8 participants. Groups included adults with long-term health conditions, young people, physically active adults, data experts, and members of the voluntary sector. Each group lasted 60-90 min, was audio recorded and transcribed verbatim. We analysed the data using thematic analysis to address the question "What are people's beliefs about making a Personal Health Record have relevance and impact?" Results We found four themes. Making it work for me is about how to encourage individuals to actively engage with their PHR. I control my information is about individuals deciding what to share and who to share it with. My concerns is about individuals' concerns about information security and if and how their information will be acted upon. Potential impact shows the potential benefits of a PHR such as increasing self-efficacy, uptake of health-protective behaviours, and professionals taking a more holistic approach to providing care and facilitating behaviour change. Conclusions Our research shows the functionality that a PHR requires in order for people to engage with it. Interactive functions and integration with lifestyle and health apps are particularly important. A PHR could increase the effectiveness of behaviour change apps by specifying evidence-based behaviour change techniques that apps should incorporate. A PHR has the potential to increase health-protective behaviours and facilitate a more person-driven health and social care system. It could support patients to take responsibility for self-managing their health and treatment regimens, as well as helping patients to play a more active role when care transfers across boundaries of responsibility.